1996
DOI: 10.1007/bf00132267
|View full text |Cite
|
Sign up to set email alerts
|

A reexamination of corporate sell-offs of real estate assets

Abstract: This article reexamines the now generally accepted notion that sell-offs of real estate assets provide positive returns for sellers but not for buyers. Following previous research, we use event study methods, but we modify the conventional market model to permit its residuals (unexpected returns) to be described by a time-varying conditional variance. We also differ from previous work in that our sample contains only sell-offs that can be precisely dated. Although we find substantial evidence of time-varying v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…A separate stream of literature examines the special case in which it is real estate assets that are sold. The consistent finding is that selling firm shareholders experience significantly positive announcement-period abnormal returns in the 1-3% range when conventional firms sell real estate assets (Glascock, Davidson and Sirmans 1991, Ball, Rutherford and Shaw 1993, Booth, Glascock and Sarkar 1996. Different from the case for conventional firms selling other kinds of real assets, in explaining abnormal returns in real estate sales, scholars have focused on tax benefits and asset valuation errors.…”
Section: Sell-offs Of Real Estatementioning
confidence: 99%
“…A separate stream of literature examines the special case in which it is real estate assets that are sold. The consistent finding is that selling firm shareholders experience significantly positive announcement-period abnormal returns in the 1-3% range when conventional firms sell real estate assets (Glascock, Davidson and Sirmans 1991, Ball, Rutherford and Shaw 1993, Booth, Glascock and Sarkar 1996. Different from the case for conventional firms selling other kinds of real assets, in explaining abnormal returns in real estate sales, scholars have focused on tax benefits and asset valuation errors.…”
Section: Sell-offs Of Real Estatementioning
confidence: 99%
“…Owers and Rogers (1986) find positive abnormal returns for corporate sellers of real estate, but they find ambiguous and inconclusive results for a small sample of 16 buyers. Glascock, Davidson and Sirmans (1991) study a sample of 51 real estate portfolio purchases during 1971-1986, and Booth, Glascock and Sarkar (1996 study a sample of 94 such transactions during 1980-1989. Both studies find that returns to acquirers are insignificantly different from zero. McIntosh, Ott and Liang (1995) study a sample of 54 major property acquisitions during in which all of the acquirers are REITs.…”
Section: The Literature On Real Estate Portfolio Transactionsmentioning
confidence: 99%
“…The empirical evidence, however, remains inconclusive. In the real estate literature, while some studies have reported positive abnormal gains (Allen and Sirmans 1987, Campbell, Ghosh and Sirmans 2001, Li, Elayan and Meyer 2001, Campbell, Petrova and Sirmans 2003), others have reported returns to REIT acquirers that are insignificantly different from zero (Glascock, Davidson and Sirmans 1991, Pierzak 2001, Booth, Glascock and Sarkar 1996). In a competitive market where there are numerous buyers in the market and the product is unique, the economic gain is captured mostly by the vendor.…”
mentioning
confidence: 99%